Cost control of cold chain delivery for logistics companies - Xiao, Xinyi (BOHR International Journal of Operations Management Research and Practices, 2023)
With the continuous development and application of modern logistics technology, logistics cost has become one of the important factors of enterprise competition. For the special field of cold chain logistics distribution, cost control is particularly critical. By studying the control method of cold chain distribution cost, this paper introduces how to reasonably optimize the distribution cost while effectively controlling the distribution cost so as to improve the competitiveness of enterprises. This paper sorts out the relevant theoretical overview and conceptual analysis and analyses the current situation of cold chain distribution cost control in logistics companies. Then, the existing logistics cost control system is evaluated, and the hierarchical analysis method and model comprehensive evaluation method are used to analyse the current control system score and problems that require additional attention and find the cause of the problem. Finally, rectification suggestions are put forward to improve distribution costs to enhance the competitive strength of enterprises.